Hubungan Pengetahuan dengan Kepatuhan Minum Obat pada Pasien Tuberkulosis Paru - Christine Handayani Siburian; Santo Damerius Silitonga; Eka Nugraha V Naibaho (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Tuberculosis (TB) is an acute or chronic infection caused by the bacterium Mycobacterium Tuberculosis. Knowledge of tuberculosis is very important in curing disease. Knowledge is what people know about health and illness or health. The cure for tuberculosis patients is greatly influenced by adherence to taking tuberculosis medication. Compliance with taking medication is an adherent behavior towards treatment that requires the willingness of the patient and establishes a rule that has been agreed upon between the health care provider and the patient. The purpose of this study was to determine the relationship between knowledge and medication adherence in pulmonary tuberculosis patients. The research design used is Cross Sectional. Samples were 31 pulmonary tuberculosis patient respondents at the Somambawa Health Center, Somambawa District, South Nias Regency. The sampling technique was purposive sampling. Collecting research data using a questionnaire of knowledge of pulmonary tuberculosis patients and Morisky Medication Adherence Sacle (MMAS). Data were analyzed with the Spearman Rho correlation test. The results showed that there was a relationship between knowledge and medication adherence in tuberculosis patients (p=0.008, r=0.466). The results of this study can recommend that the need for nursing actions that can increase knowledge so that adherence in taking medication also increases.